1998
DOI: 10.1152/ajpregu.1998.275.3.r870
|View full text |Cite
|
Sign up to set email alerts
|

Acute stressor exposure both suppresses acquired immunity and potentiates innate immunity

Abstract: Acute stressor exposure alters immune function. Rats exposed to inescapable tail shock stress (IS) generate less antibody to a benign, antigenic protein, keyhole limpet hemocyanin (KLH). The following studies examined the effect of IS on peritoneal cavity, spleen, and mesenteric lymph node cell number, interferon-γ (IFN-γ) production, and nitrite production. Rats were injected intraperitoneally with KLH (200 μg) or saline immediately before IS exposure and killed 0, 48, and 96 h after IS termination. KLH immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
2
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 28 publications
8
46
2
2
Order By: Relevance
“…Moreover, when splenic macrophages from mice exposed to SDR were incubated with the iNOS inhibitor L-NMMA (a synthetic form of arginine that cannot be converted to produce nitric oxide), this increase in stress-induced killing was abolished. This finding is consistent with reports from others that have shown that stressor exposure can enhance macrophage phagocytosis (46) and microbicidal activity through the enhanced production of nitric oxide (23,25,32). It is not likely that nitric oxide was directly responsible for the enhanced microbicidal activity since nitric oxide has only moderate microbicidal activity in comparison to other reactive species (13,16,47).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, when splenic macrophages from mice exposed to SDR were incubated with the iNOS inhibitor L-NMMA (a synthetic form of arginine that cannot be converted to produce nitric oxide), this increase in stress-induced killing was abolished. This finding is consistent with reports from others that have shown that stressor exposure can enhance macrophage phagocytosis (46) and microbicidal activity through the enhanced production of nitric oxide (23,25,32). It is not likely that nitric oxide was directly responsible for the enhanced microbicidal activity since nitric oxide has only moderate microbicidal activity in comparison to other reactive species (13,16,47).…”
Section: Discussionsupporting
confidence: 92%
“…This enhanced immune activity can be adaptive, particularly in laboratory animals challenged with bacteria (7,15,23,32) or during squamous cell carcinoma (26). It must be recognized, however, that the reactive molecules modified upon stressor exposure have important roles in numerous physiologic responses that can tip the balance between health and disease (9,20,42,64).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those reported by Liu et al, who showed that IFN-γ was lower in the spleen of pigeons exposed to avermectin (Liu et al 2014a). Another study showed that the downregulation of IFN-γ causes a decrease in the immune function of chickens (Fleshner et al 1998). We observed that IFN-γ was lower in the bursa of Fabricius of chickens fed a Sedeficient diet, which exhibited poor immune function and may cause bursal injury.…”
Section: Discussionsupporting
confidence: 93%
“…Animals either remained undisturbed in their home cages as controls (no stress) or were exposed to inescapable tail shock (stress) (Fleshner et al 1998;Campisi et al 2002a). Stressed rats were transported to an adjacent room and placed in Plexiglas restraining tubes (15 ϫ 7 cm).…”
Section: Inescapable Tail Shock Proceduresmentioning
confidence: 99%
“…The total stress session lasted approximately 100 minutes. This acute laboratory stressor has been reported to increase NO (Fleshner et al 1998;Campisi et al 2002a) and proinflammatory cytokines (Johnson et al 2002) after antigen challenge as well as activate the autonomic nervous system (Fleshner 2000) and the hypothalamic-pituitary-adrenal axis (Fleshner et al 1993), and induce synthesis of iHsp72 in a variety of tissues (Campisi et al 2002b).…”
Section: Inescapable Tail Shock Proceduresmentioning
confidence: 99%